Materials for nanostructured organic devices: theoretical and experimental studies of donors and acceptors - Citolino, Lucas Vinicius de Lima [UNESP] (2022)
The frontier energy levels of conjugated polymers are critical to their performance in organic electronic devices. In organic solar cells the magnitude of the HOMO and LUMO levels directly affects parameters, such as the short circuit current and the open-circuit voltage, which are very important to achieve high efficiency. Accordingly, density functional theory (DFT) has become useful to model orbital energies of conjugated organic molecules. But, performing DFT calculations on conjugated polymers is challenging due to their size (large number of atoms), besides the problems to predict accurate values for virtual orbitals. In this context, the main aim of this work is set out the general considerations for the use of DFT approaches in organic molecules with large number of atoms, in particular when one has to describe one or more electronic states of more or less strongly correlated electrons. Thereby, a series of DFT calculations were performed, using different basis set and functionals, in singlet and triplet states on a set of promising donor-acceptor pairs to estimate accurate values on molecular orbital energies. In addition, DFT calculations was used to optimise the molecular geometries and determine energies of unpublished polyfullerenes to compare with Langmuir-Schaefer thin films properties. To obtain experimentally the HOMO and LUMO from polyfullerenes thin films, measurements of absorption were performed using Ultraviolet-visible spectroscopy and electrical characterizations were carried out through cyclic voltammetry measurements. In a series of DFT calculations in singlet state, with different functionals and basis set, the B3LYP functional together with 6-311G(d,p) basis set give the best values for HOMO and LUMO. For saving computational resources, 6-31G(d) can be used to provide good values for energy levels from frontier molecular orbitals. For donors, the correlation between the LUMO calculated with experimental results is too poor, while for acceptors, is acceptable. The DFT calculations in triplet states give good correlation for donors, where the LUMO energy is most accurately approximated from the αHOMO energy. In the study of polyfullerene thin films, the π-A isotherms indicated that depending on the solvent, the arrangement of molecules is altered, indicating higher solubility and lower level of aggregation, and vice versa. In UV-Vis and CV measurements the influence of solvent is also evidenced being directly related to the maximum absorption and difference in the position of the absorption peak, and also to shifting of oxidation and reduction peaks. In the junction between DFT calculations and CV and UV-Vis measurements, the DFT/B3LYP/6-31+G(d) method provide LUMO values close to experimental values, thus being an important tool for comparing results, since there is no previous literature from these exact polyfullerenes.